2012
DOI: 10.1186/1746-6148-8-201
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Salmonella spp. serovars isolated from the intestines of water buffalo calves with gastroenteritis

Abstract: BackgroundSalmonellosis in water buffalo (Bubalus bubalis) calves is a widespread disease characterized by severe gastrointestinal lesions, profuse diarrhea and severe dehydration, occasionally exhibiting a systemic course. Several Salmonella serovars seem to be able to infect water buffalo, but Salmonella isolates collected from this animal species have been poorly characterized. In the present study, the prevalence of Salmonella spp. in water buffalo calves affected by lethal gastroenteritis was assessed, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
19
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 22 publications
6
19
0
3
Order By: Relevance
“…Our study of the distribution of various fimbrial genes in Salmonella serovars from poultry in China has shown that over 70% of the isolates possessed the bcfD, csgA, fimA, stdB, sthE, stbD, lpfD, stfH, stiH, safC, and steB genes, which is consistent with previous studies (10,34) and provides further evidence that these fimbrial genes are widely distributed among S. enterica. We found lower prevalences of tcfA, stkA, pefA, sefA, pegD, stcA, and stjA (11.8 to 55.7%) and no evidence of staA and stgA, two genes which were once reported in S. Pullorum from poultry, suggesting that some fimbrial genes might be serovar specific (10,12).…”
Section: Discussionsupporting
confidence: 91%
“…Our study of the distribution of various fimbrial genes in Salmonella serovars from poultry in China has shown that over 70% of the isolates possessed the bcfD, csgA, fimA, stdB, sthE, stbD, lpfD, stfH, stiH, safC, and steB genes, which is consistent with previous studies (10,34) and provides further evidence that these fimbrial genes are widely distributed among S. enterica. We found lower prevalences of tcfA, stkA, pefA, sefA, pegD, stcA, and stjA (11.8 to 55.7%) and no evidence of staA and stgA, two genes which were once reported in S. Pullorum from poultry, suggesting that some fimbrial genes might be serovar specific (10,12).…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with other studies, substantial variability was observed in the occurrence of phage genes among the 79 Salmonella isolates in our study (Borriello et al, 2012;Drahovska et al, 2007). The acquisition and the loss of prophage-associated…”
Section: The Office International Des éPizooties Reference Laboratorysupporting
confidence: 93%
“…The ability of nontyphoidal Salmonella to cause invasive disease is attributed to arrays of virulence genes defined in the Salmonella pathogenicity islands (SPIs). The avrA, ssaQ, mgtC, siiD, and sopB genes are genetic markers for the presence of the SPI 1-5 in Salmonella, although their presence does not necessarily implicate the presence of the entire SPI (Borriello et al, 2012). In our study, except one isolate was negative for mgtC, siiD and sopB, and four isolates for sopB, the remaining isolates all harbored the five SPI genes, indicating that these virulence genes are widespread and highly conserved among Salmonella as previously reported (Graziani et al, 2011;Huehn et al, 2010).…”
Section: The Office International Des éPizooties Reference Laboratorymentioning
confidence: 99%
See 1 more Smart Citation
“…The plasmid-associated gene spvC is often detected in S. Enteritidis and a few other Salmonella serovars; it was found in more than 80% of the isolates we tested [27]. The avrA, ssaQ, mgtC, siiD, and sopB genes were highly conserved and were genetic markers for the presence of the SPI 1-5 in Salmonella [28]. The high percentage of these virulence genes in our study also indicated that they were widespread and highly conserved.…”
Section: Discussionsupporting
confidence: 58%